La OTAN tras la Cumbre de Riga: la puerta sigue abierta - Priego, Alberto (UNISCI Discussion Papers, 2007)
In Riga, the capital of Latvia, NATO held its latest summit. It has been the Summit of the reconciliation. There, members of NATO adopted the fundamental guidelines for the future of the Alliance. Among the most important topics were the Global Partners initiative, the situation in Afghanistan or the transformation of NATO which started in Praga (2002), etc. Nevertheless, the most important issue for the following years could be the integration of Georgia and Ukraine into NATO. We can summarize the Summit in the following statement made by George W. Bush: “NATO’s door remains open”.